ANALISIS PROSES BISNIS DAN PERANCANGAN SISTEM INFORMASI KEUANGAN PADA RESTAURANT INDIAN FOOD DELHI6 BERBASIS MICROSOFT EXCEL VB - Paramitha, I Gusti Agung Diah Pradnya; Juliharta, I Gede Putu Krisna; Alam, Helmy Syakh (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
Accounting information systems are the backbone of every company, including restaurants. Restaurant Indian Food Delhi6, as a fastfood restaurant operating in Bali, currently still relies on manual methods to record and manage its financial transactions. Although this manual method was effective in the past, along with the increasing number of transactions and business complexity, it began to show a number of weaknesses. To overcome these problems, this study aims to design and develop an integrated VBA Excel-based accounting information system specifically for Restaurant Indian Food Delhi6. This system is expected to automate various repetitive accounting tasks, such as recording sales, purchases, and payroll, thereby reducing employee workload and minimizing human error. In developing this system, the Waterfall and UML methods will be used. The Waterfall method will be used as a framework for overall system development, while UML will be used to model and document various aspects of the system, such as use cases, flowcharts, and class diagrams. The final result of this study is a comprehensive accounting information system design, including use cases, narratives, and an integrated financial system. This system is expected to meet the specific needs of Restaurant Indian Food Delhi6 and be an effective solution to overcome current problems.